Changes in distance decay relationships after river regulation: similarity among fish assemblages in a large Amazonian river. Issue 4 (9th April 2013) - Araújo, Ercilia S.; Marques, Elineide E.; Freitas, Iriene S.; Neuberger, Andréa L.; Fernandes, Rodrigo; Pelicice, Fernando M.
Abstract: The construction of large dams has changed natural hydrology of many rivers in South America. Considering that little is known about the reorganisation of nonmigratory fish assemblages following an impoundment, we investigated changes caused by the construction of Lajeado Dam on the spatial distribution of nonmigratory fish along the Tocantins River, a large Amazonian river. In particular, we investigated changes in distance decay of community similarity (initial similarity and halving distance) in periods that preceded and followed the construction of the dam. For this study, we analysed data collected over a four‐year period, including seven sites distributed along the Tocantins River ( 270 km). Initial similarity showed high values and little variation over the years. Halving distance, on the other hand, changed considerably after impoundment, showing progressive smaller values. In the first 2 years after impoundment, halving distance decreased by more than half of the initial value, indicating changes in distance decay relationships. An ordination analysis nonmetric multidimensional scaling (NMDS) indicated substantial changes in assemblage structure between pre‐ and postimpoundment periods, especially in sites close to the dam. In addition, after river regulation, we recorded shifts in species abundance across sites, while numerical dominance increased and local richness decreased in sites near the dam. Our results indicate that the dam changed diversity gradients along the river corridor, increasing the distance decay of assemblage similarity. All these findings evidence that nonmigratory fish assemblages are particularly vulnerable to river regulation.